The Management of Rheumatoid Arthritis Patient at Rural Siddha Hospital, Kodikamam, Jaffna, Srilanka - Miraaj, R.; Miraaj, V. (Archers & Elevators Publishing House, 2019)
The Rheumatoid arthritis is a chronic, systemic inflammatory disorder that mainly attacks the joints. It also affects several tissues and organs such as lungs, pleura, pericardium, heart, and sclera. This produces an inflammatory sinovitis that often progresses to the destruction of the articular cartilage and ankylosis of the joints. About 1%of the world’s population is affected by rheumatoid arthritis. Women are affected three times more often than men. Onset is most frequent between the ages of 40 and 50 but people of any age can be affected. In siddha medicine the same clinical symptoms are described under the Vali Azhal keel vayu. This is an observational case study and it was conducted at Rural Siddha Hospital, Kodikamam, Jaffna. The permission for this study from the MOIC, Rural Siddha Hospital, Kodikamam, Jaffna. Patient consent was taken for this study in written from to take necessary photographs. One female known Rheumatoid arthritis patient was selected and she was treated three weeks in the ward. Siddha and Ayurvedic drugs only were given internally and externally. More over the dietary regiments also were advised. Before and after the treatment the progresses of the disease were recorded as photograph and on BHT. The Rheumatoid factor was 46IU/L after the treatment while it was 185IU/L Before treatment. The pain and swelling of Right knee joint were markedly decreased after the treatment and the degree of swelling and pain were estimated in certain conditions. There for according this clinical observation we can recommend this treatment method as an efficient method for management of rheumatoid arthritis patients.
Keywords: Rheumatoid arthritis; Management